Evaluation of modeled cloud chemistry mechanism against laboratory irradiation experiments: The HxOy/iron/carboxylic acid chemical system - Long, Yoann; Charbouillot, Tiffany; Brigante, Marcello; Mailhot, Gilles; Delort, Anne-Marie; Chaumerliac, Nadine; Deguillaume, Laurent (Atmospheric environment (1994), 2013)
Currently, cloud chemistry models are including more detailed and explicit multiphase mechanisms based on laboratory experiments that determine such values as kinetic constants, stability constants of complexes and hydration constants. However, these models are still subject to many uncertainties related to the aqueous chemical mechanism they used. Particularly, the role of oxidants such as iron and hydrogen peroxide in the oxidative capacity of the cloud aqueous phase has typically never been validated against laboratory experimental data. To fill this gap, we adapted the M2C2 model (Model of Multiphase Cloud Chemistry) to simulate irradiation experiments on synthetic aqueous solutions under controlled conditions (e.g., pH, temperature, light intensity) and for actual cloud water samples. Various chemical compounds that purportedly contribute to the oxidative budget in cloud water (i.e., iron, oxidants, such as hydrogen peroxide: H2O2) were considered. Organic compounds (oxalic, formic and acetic acids) were taken into account as target species because they have the potential to form iron complexes and are good indicators of the oxidative capacity of the cloud aqueous phase via their oxidation in this medium. The range of concentrations for all of the chemical compounds evaluated was representative of in situ measurements. Numerical outputs were compared with experimental data that consisted of a time evolution of the concentrations of the target species. The chemical mechanism in the model describing the “oxidative engine” of the HxOy/iron (HxOy = H2O2, HO2/O2− and HO) chemical system was consistent with laboratory measurements. Thus, the degradation of the carboxylic acids evaluated was closely reproduced by the model. However, photolysis of the Fe(C2O4)+ complex needs to be considered in cloud chemistry models for polluted conditions (i.e., acidic pH) to correctly reproduce oxalic acid degradation. We also show that iron and formic acid lead to a stable complex whose photoreactivity has currently not been investigated. The updated aqueous chemical mechanism was compared with data from irradiation experiments using natural cloud water. The new reactions considered in the model (i.e., iron complex formation with oxalic and formic acids) correctly reproduced the experimental observations. •We model irradiation experiments on synthetic solutions with a cloud chemistry model.•We examine the time evolutions of some target species (iron, hydrogen peroxide, carboxylic acids).•The aqueous chemical mechanism in the model is consistent with laboratory measurements.•We report that some interactions between iron and carboxylic acids are not correctly represented in cloud chemistry models.